The use of electronic information resources among the users of the Penang Public Library Corporation / Hashimah Mohamed Yusoff - Hashimah , Mohamed Yusoff (2005)
Public libraries place importance on information technology for the delivery of quality services. One aspect of quality services is knowing the usage in the electronic information resources (EIRs) among the library users. This study was done to investigate the use of the EIRs at the Penang Public Library Corporation (PPLC). This study employed a multi-method approach to collect data; including a printed questionnaire survey, group interview, observations, and examination of documents. The data was analyzed using SPSS Version 12.00. The findings revealed that EIRs services provided by PPLC are being regularly used by the users. It was found out that the younger group relied more on the EIRs. The most preferred EIRs were Internet (51.9%) and OPAC (43.2%). The preference of Internet was higher among school students with 25% users and college students with 1 7 .2% users, whereas preference of OP AC was higher among the professional group with 30% users. It was found out that most of the users who used Internet were for information searching. For OP AC, they seemed more likely to use title search in searching library materials and they learned to use the OP AC by themselves. The usage of other EIRs were less popular with Electronic Journals (19.1 %), Online databases (16.0%) and CD-ROMs (7.4%). Therefore, PPLC must strive aggressively to promote the less popular EIRs which are provided but seldom used by the library users. PPLC needs to improve its training programme in order to help users to enhance the use of EIRs.